Resolver la siguiente operación algebraica
(6x4 - 7x3 + 5x - 2) restar
(3x4 - 6x2 + 3x + 4x3 - 4)
Respuestas
Respuesta dada por:
2
Respuesta:
3x4-11x3+6x2+2x+2
Explicación paso a paso:
6x4 -7x3 +5x -2 - (3x4 - 6x2 + 3x + 4x3 - 4)
= 6x4 -7x3 +5x -2 -3x4 + 6x2 -3x - 4x3 + 4
=(6x4-3x4)+(-7x3-4x3)+6x2+(5x-3x)+(-2+4)
= 3x4-11x3+6x2+2x+2
Respuesta dada por:
1
Respuesta:
3x4-11x3+6x2+2x+2
Explicación paso a paso:
6x4 -7x3 +5x -2 - (3x4 - 6x2 + 3x + 4x3 - 4)
= 6x4 -7x3 +5x -2 -3x4 + 6x2 -3x - 4x3 + 4
=(6x4-3x4)+(-7x3-4x3)+6x2+(5x-3x)+(-2+4)
= 3x4-11x3+6x2+2x+2
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años